A negative electrode material for nickel-zinc battery and preparation method thereof, negative electrode sheet, and battery

By coating the polyethylene glycol-polyaniline copolymer on the zinc oxide surface of the nickel-zinc battery and introducing appropriate active substances into the negative electrode sheet, the problem of easy dissolution of the zinc negative electrode leads to low battery life is solved, and the circulation performance and storage capacity of the battery are significantly improved.

CN119133419BActive Publication Date: 2025-02-28SHENZHEN HIGHPOWER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411598048.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-28
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The zinc negative electrode of existing nickel-zinc batteries is easily dissolved, resulting in low battery life, affecting the battery's circulation performance and storage capacity.

Method used

By coating the polyethylene glycol-polyaniline copolymer on the surface of zinc oxide, corrosion dissolution of zinc oxide in the alkaline electrolyte is inhibited, and appropriate combinations of active substances are introduced into the negative electrode sheet to improve electrochemical capacity and corrosion resistance.

Benefits of technology

It effectively inhibits the dissolution of zinc negative electrode and dendrites, improves the capacity recovery ability of nickel-zinc batteries after long-term storage and storage, and reduces electrode polarization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

In order to solve the problem that the zinc negative electrode of the existing nickel-zinc battery is easily soluble, resulting in a short battery life, the present invention provides a negative electrode material for a nickel-zinc battery and a preparation method thereof, a negative electrode sheet, and a battery. The negative electrode material for the nickel-zinc battery includes zinc oxide and a coating layer coated on the surface of the zinc oxide, and the coating layer includes a polyethylene glycol-polyaniline copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a negative electrode material for a nickel-zinc battery and a preparation method thereof, a negative electrode sheet, and a battery. Background Art

[0002] Nickel-zinc battery is a green and environmentally friendly battery that can replace nickel-metal hydride and lead-acid batteries. Compared with nickel-metal hydride and nickel-cadmium batteries, it has the characteristics of high voltage and strong discharge current, and has unparalleled advantages in digital cameras, flashlights, and electric toys. Compared with lead-acid batteries, it is green and environmentally friendly, has high specific power, high specific energy, and good low-temperature performance.

[0003] However, the short life of existing nickel-zinc batteries is the main problem that has long restricted the development of nickel-zinc batteries. The main reason for the short life of nickel-zinc batteries is the corrosion and uneven deposition of zinc, the negative active material, in alkaline electrolytes. The corrosion of zinc and zinc oxide leads to the loss of active materials, forming a passivation layer, reducing the electrochemical surface area, and causing irreversible capacity loss during the cycle. In alkaline electrolytes, zinc redeposition is easy to occur on the surface of the pole piece, and this loose deposition will become "dead zinc" during the battery cycle, resulting in capacity decay and accelerating premature battery failure. In addition, zinc dissolves and forms zinc dendrites along the ion transfer direction, which may connect to the positive electrode through the micropores of the diaphragm to form a micro-short circuit. At the same time, the zinc negative electrode continues to melt during storage and circulation. As the ion transfer process occurs, the zinc content in the nickel positive electrode gradually increases, increasing the interlayer spacing of the positive active material nickel hydroxide, causing the nickel hydroxide to expand and break in volume, and then the positive electrode capacity is irreversibly decayed. Therefore, how to inhibit the dissolution of the zinc negative electrode to improve the battery's cycle performance is the focus of battery research. Summary of the invention

[0004] In view of the problem that the zinc negative electrode of the existing nickel-zinc battery is easily soluble, resulting in a short battery life, the present invention provides a negative electrode material for a nickel-zinc battery and a preparation method thereof, a negative electrode sheet, and a battery.

[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0006] In a first aspect, the present invention provides a negative electrode material for a nickel-zinc battery, comprising zinc oxide and a coating layer coated on the surface of the zinc oxide, wherein the coating layer comprises a polyethylene glycol-polyaniline copolymer.

[0007] Optionally, the coating layer has a thickness of 10-20 nm.

[0008] Optionally, the mass ratio of the zinc oxide to the polyethylene glycol-polyaniline copolymer is (8-15):1.

[0009] In a second aspect, the present invention further provides a method for preparing a negative electrode material for a nickel-zinc battery as described in any one of the above, comprising the following steps:

[0010] Dispersing polyethylene glycol, aniline and dodecylbenzene sulfonic acid in water to obtain an emulsion; adding ammonium peroxodisulfate to the emulsion to react and obtain a polyethylene glycol-polyaniline copolymer;

[0011] The polyethylene glycol-polyaniline copolymer and zinc oxide are dispersed in a solvent, filtered and dried to obtain zinc oxide coated with the polyethylene glycol-polyaniline copolymer.

[0012] Optionally, the molar ratio of the polyethylene glycol, aniline, dodecylbenzenesulfonic acid and ammonium peroxodisulfate is (0.5-2): (0.5-2): (2-5): (0.5-2).

[0013] Optionally, the molecular weight of the polyethylene glycol is 200-600 g / mol.

[0014] In a third aspect, the present invention further provides a negative electrode sheet, comprising a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises the negative electrode material for a nickel-zinc battery as described in any one of the above items, or the negative electrode material for a nickel-zinc battery prepared by the preparation method of the negative electrode material for a nickel-zinc battery as described in any one of the above items.

[0015] Optionally, the active material layer includes 55%~60% polyethylene glycol-polyaniline copolymer-coated zinc oxide, 5%~10% zinc powder, 1%~5% calcium zincate, 0.5%~2% bismuth oxide, 0.05%~0.1% indium oxide, 0.01%~0.5% sodium dodecylbenzene sulfonate, 1%~2% chopped fibers and 25%~30wt% binder.

[0016] In a fourth aspect, the present invention provides a battery comprising a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet as described above; the electrolyte comprises a hydroxide having the formula M (OH), where M is selected from one or more of K, Na, Li, Al and Zn.

[0017] Optionally, the electrolyte further includes one or more of ZnO, a buffer, and sodium phytate.

[0018] Optionally, the buffer comprises phosphate;

[0019] And / or, the molar concentration of ZnO in the electrolyte is 0.3M~1M;

[0020] And / or, the molar concentration of sodium phytate in the electrolyte is 0.05M~0.3M.

[0021] Optionally, the injection amount of the electrolyte is 20% to 30% of the sum of the mass of the positive electrode sheet and the negative electrode sheet.

[0022] In the present invention, by coating the zinc oxide surface with a coating layer formed by a polyethylene glycol-polyaniline copolymer, the corrosion and dissolution of zinc oxide in an alkaline electrolyte are greatly reduced, thereby inhibiting the dendrite growth and electrode deformation caused by the dissolution of the active material in the zinc negative electrode, and effectively improving the long-term storage and post-storage capacity recovery capabilities of the nickel-zinc battery. At the same time, the hydrophilic polyethylene glycol in the polyethylene glycol-polyaniline copolymer improves the conductivity of the coating layer and reduces electrode polarization.

[0023] The active material layer in the negative electrode sheet introduces zinc oxide coated with polyethylene glycol-polyaniline copolymer to inhibit the dendrite growth and electrode deformation caused by the dissolution of the active material in the zinc negative electrode. The electrochemical capacity of the negative electrode is increased by adding zinc powder in the active material layer. The solubility of zinc in alkaline electrolyte is reduced by adding calcium zincate. The overpotential of hydrogen evolution at the negative electrode is increased by adding indium oxide and bismuth oxide, while the growth of zinc dendrites is inhibited. The toughness of the electrode sheet is enhanced by adding chopped fibers, and the powder removal condition of the electrode sheet is improved. Sodium dodecylbenzene sulfonate is added to form a fluffy insulating layer on the surface of the negative electrode to slow down the corrosion of the negative electrode active material. DETAILED DESCRIPTION

[0024] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0025] An embodiment of the present invention provides a negative electrode material for a nickel-zinc battery, comprising zinc oxide and a coating layer coated on the surface of the zinc oxide, wherein the coating layer comprises a polyethylene glycol-polyaniline copolymer.

[0026] In the present invention, by coating the zinc oxide surface with a coating layer formed by a polyethylene glycol-polyaniline copolymer, the corrosion and dissolution of zinc oxide in an alkaline electrolyte are greatly reduced, thereby inhibiting the dendrite growth and electrode deformation caused by the dissolution of the active material in the zinc negative electrode, and effectively improving the long-term storage and post-storage capacity recovery capabilities of the nickel-zinc battery. At the same time, the hydrophilic polyethylene glycol in the polyethylene glycol-polyaniline copolymer improves the conductivity of the coating layer and reduces electrode polarization.

[0027] In some embodiments, the coating layer has a thickness of 10-20 nm. Within this thickness range, the coating layer can further inhibit the corrosion and dissolution of zinc oxide in alkaline electrolyte, and reduce the dendrite growth and electrode deformation of the zinc negative electrode.

[0028] In a specific embodiment, the thickness of the coating layer includes but is not limited to 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm.

[0029] In some embodiments, the mass ratio of the zinc oxide to the polyethylene glycol-polyaniline copolymer is (8-15): 1. By limiting the mass ratio of zinc oxide to the polyethylene glycol-polyaniline copolymer, the zinc oxide can be better coated by the polyethylene glycol-polyaniline copolymer to form a coating layer.

[0030] In a specific embodiment, the mass ratio of zinc oxide to the polyethylene glycol-polyaniline copolymer includes but is not limited to 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1.

[0031] In a second aspect, an embodiment of the present invention further provides a method for preparing a negative electrode material for a nickel-zinc battery as described in any one of the above, comprising the following steps:

[0032] Polyethylene glycol, aniline and dodecylbenzene sulfonic acid are dispersed in water to obtain an emulsion; ammonium peroxodisulfate is added to the emulsion to react and obtain a polyethylene glycol-polyaniline copolymer; specifically, polyethylene glycol and aniline are first dispersed in water, stirred for 2 hours, and then dodecylbenzene sulfonic acid is added to form a stable emulsion. When adding ammonium peroxodisulfate to the emulsion, it is added dropwise, at 0°C, a speed of 40r / min, and reacted for 4 hours to obtain a polyethylene glycol-polyaniline copolymer crude product, and the polyethylene glycol-polyaniline copolymer crude product is washed with water, and then vacuum dried at 60°C for 12 hours to obtain a polyethylene glycol-polyaniline copolymer.

[0033] The polyethylene glycol-polyaniline copolymer and zinc oxide are dispersed in a solvent, filtered and dried to obtain zinc oxide coated with the polyethylene glycol-polyaniline copolymer. Specifically, the solvent is anhydrous ethanol, and the polyethylene glycol-polyaniline copolymer is dissolved in ethanol to coat the zinc oxide.

[0034] In some embodiments, the molar ratio of polyethylene glycol, aniline, dodecylbenzene sulfonic acid and ammonium peroxodisulfate is (0.5-2): (0.5-2): (2-5): (0.5-2). By limiting the molar ratio of polyethylene glycol and aniline, the content of polyethylene glycol and polyaniline in the polyethylene glycol-polyaniline copolymer is limited to adjust the conductivity and anti-corrosion performance of the coating layer.

[0035] In some embodiments, the molecular weight of the polyethylene glycol is 200-600 g / mol. By controlling the molecular weight of the polyethylene glycol, the molecular weight of the polyethylene glycol-polyaniline copolymer is controlled, so that the polyethylene glycol-polyaniline copolymer can better coat zinc oxide.

[0036] In a third aspect, an embodiment of the present invention further provides a negative electrode sheet, comprising a current collector and an active material layer disposed on at least one side of the current collector, wherein the active material layer comprises the negative electrode material for a nickel-zinc battery as described in any one of the above, or the negative electrode material for a nickel-zinc battery prepared by the method for preparing the negative electrode material for a nickel-zinc battery as described in any one of the above. The active material layer in the negative electrode sheet introduces zinc oxide coated with a polyethylene glycol-polyaniline copolymer, thereby inhibiting dendrite growth and electrode deformation caused by the dissolution of the active material in the zinc negative electrode.

[0037] In some embodiments, the active material layer includes 55% to 60% polyethylene glycol-polyaniline copolymer-coated zinc oxide, 5% to 10% zinc powder, 1% to 5% calcium zincate, 0.5% to 2% bismuth oxide, 0.05% to 0.1% indium oxide, 0.01% to 0.5% sodium dodecylbenzene sulfonate, 1% to 2% chopped fibers, and 25% to 30 wt % binder.

[0038] The electrochemical capacity of the negative electrode is increased by adding zinc powder to the active material layer. The solubility of zinc in alkaline electrolyte is reduced by adding calcium zincate. The overpotential of hydrogen evolution at the negative electrode is increased by adding indium oxide and bismuth oxide, while the growth of zinc dendrites is inhibited. The toughness of the pole piece is enhanced by adding chopped fibers, and the powder removal condition of the pole piece is improved. Sodium dodecylbenzene sulfonate is added to form a fluffy insulating layer on the surface of the negative electrode to slow down the corrosion of the negative electrode active material.

[0039] Specifically, the chopped fibers are suspended from the chopped fibers of PA66. The binder includes a 2% CMC aqueous solution (carboxymethyl cellulose aqueous solution), a 60% PTFE aqueous solution (polytetrafluoroethylene aqueous solution) and PVA (polyvinyl alcohol).

[0040] In a fourth aspect, an embodiment of the present invention provides a battery, comprising a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet as described above; the electrolyte comprises a hydroxide having the formula M (OH), and M is selected from one or more of K, Na, Li, Al and Zn. The separator can absorb alkali solution and insulate to prevent short circuits, and adopts a dendrite-proof composite separator of a layer of non-woven fabric and three layers of PE (Polyethylene, polyethylene), or a dendrite-proof composite separator of a layer of non-woven fabric and three layers of PP. The positive electrode sheet is faced with an alkali-absorbing non-woven fabric that has been hydrophilized by sulfonation or grafting, and the negative electrode sheet is faced with a three-layer PE microporous separator or a three-layer PP microporous separator that has been hydrophilized by sulfonation or grafting.

[0041] In some embodiments, the electrolyte further includes one or more of ZnO, a buffer, and sodium phytate. The dissolution of the negative electrode material in the electrolyte is inhibited by adding zinc oxide. By adding a buffer, the pH value of the electrolyte is adjusted so that the pH value of the electrolyte at 25°C is 10-14 and the conductivity is 350 mS / cm-470 mS / cm. Sodium phytate is added to chelate the zinc ions that increase during storage, thereby reducing the concentration of zinc ions in the electrolyte and reducing the negative impact of the dissolution of the negative electrode on the positive electrode. At the same time, sodium phytate absorbs the oxygen generated by overcharging of the positive electrode during the charging and discharging process, thereby inhibiting the gas production of the battery.

[0042] In some embodiments, the buffer comprises phosphate; specifically, it can be selected from one of sodium dihydrogen phosphate and sodium hydrogen phosphate.

[0043] And / or, the molar concentration of ZnO in the electrolyte is 0.3M~1M;

[0044] And / or, the molar concentration of sodium phytate in the electrolyte is 0.05 M to 0.3 M. By limiting the molar concentrations of ZnO and sodium phytate in the electrolyte, the dissolution of the negative electrode is further suppressed, and the storage performance and capacity recovery ability of the nickel-zinc battery after storage are improved.

[0045] In some embodiments, the amount of the electrolyte injected is 20% to 30% of the sum of the mass of the positive electrode sheet and the negative electrode sheet. By limiting the amount of electrolyte injected, directional zinc deposition is guided and [Zn(OH)4] 2− diffusion, thereby improving the cycle performance of nickel-zinc batteries.

[0046] The present invention is further described below by way of examples.

[0047] Example 1

[0048] This example is used to illustrate the negative electrode material for nickel-zinc battery disclosed in the present invention and its preparation method, negative electrode sheet, and battery. It includes the following steps:

[0049] Polyethylene glycol-polyaniline copolymer coated zinc oxide

[0050] 1 mol PEG-300 (molecular weight 300 g / mol) and 1 mol aniline (ANI) were dispersed in 3L deionized water and magnetically stirred for 2 h. 3 mol dodecylbenzenesulfonic acid (DBSA) aqueous solution was added to form a stable emulsion. 1 mol ammonium peroxodisulfate (APS) was gradually added to the solution, and the magnetic stirring parameters were set as: 0°C, speed 40r / min, and reaction for 4h. The precipitate obtained by the reaction was repeatedly rinsed with deionized water and then vacuum dried at 60°C for 12h to obtain polyethylene glycol-polyaniline copolymer (PEG-PANI).

[0051] Zinc oxide and polyethylene glycol-polyaniline copolymer were added into anhydrous ethanol at a mass ratio of 10:1 and magnetically stirred for 6 hours. The solid matter was then filtered and dried using a filter membrane to obtain zinc oxide coated with polyethylene glycol-polyaniline copolymer. The coating layer thickness was 15 nm.

[0052] Negative plate

[0053] 60% polyethylene glycol-polyaniline copolymer coated zinc oxide, 7% zinc powder, 3% calcium zincate, 1% bismuth oxide, 0.1% indium oxide, 0.4% sodium dodecylbenzene sulfonate, 1.5% PA66 chopped fibers, 27% binder (2% CMC aqueous solution, 60% PTFE aqueous solution, 38% PVA) and pure water were mixed and stirred to obtain negative electrode slurry. The negative electrode slurry was evenly applied on the copper tin-plated inclined wire mesh current collector, and then dried, rolled and cut to obtain the negative electrode sheet.

[0054] Positive electrode

[0055] 70wt%-75wt% of spherical β-Ni(OH)2 (nickel hydroxide) coated with trivalent cobalt, 0.01wt%-0.05wt% of Ca(OH)2 (calcium hydroxide), 3wt%-4wt% of Ni powder, 0.5wt%-1wt% of Y2O3 (yttrium trioxide) or 0.5wt%-1wt% of Yb2O3 (ytterbium trioxide), 2wt%-3wt% of CMC, 1wt%-2wt% of xanthan gum, and the rest of pure water are uniformly mixed to obtain positive electrode slurry. The slurry is filled and pressed into nickel foam and dried, and then rolled and cut to obtain positive electrode sheets.

[0056] Electrolyte

[0057] Dissolve NaOH and KOH in water, add ZnO and sodium phytate, mix, and then add sodium dihydrogen phosphate to adjust the pH of the electrolyte to 12. The concentration of ZnO in the electrolyte is 0.5M, and the concentration of sodium phytate is 0.1M.

[0058] Battery production:

[0059] The positive electrode sheet, separator and negative electrode sheet are wound / stacked to obtain a bare cell. The bare cell is placed in the aluminum-plastic film that has been punched out to complete the top and side sealing. After the processes of liquid injection, static, formation, capacity division, and testing, the battery is completed.

[0060] Embodiments 2 to 15

[0061] The embodiment is used to illustrate the negative electrode material for nickel-zinc battery disclosed in the present invention and its preparation method, negative electrode sheet, and battery. It includes most of the operation steps in embodiment 1, except that the formula in Table 1 is used.

[0062] Comparative Examples 1 to 3

[0063] The comparative example is used to compare and illustrate the negative electrode material for nickel-zinc battery disclosed in the present invention and its preparation method, negative electrode sheet, and battery. It includes most of the operation steps in Example 1, except that the coating layer and formulation in Table 1 are used.

[0064] Table 1

[0065]

[0066] Performance Testing

[0067] 1. The batteries prepared in the above examples and comparative examples were subjected to the following performance tests:

[0068] Use 0.2C (taking 2A1400 battery as an example, the theoretical capacity is 1400mAh, 0.2C is 280mAh) charge and discharge cycles for three times, and record the highest electrochemical capacity as the standard capacity.

[0069] The storage performance test is to place the fully charged battery at 60°C for 10 days, 20 days, and 30 days respectively. The high temperature 60°C storage simulates the storage at room temperature for 4 years. After storage, the battery is taken out and placed at room temperature for 2 hours for discharge, and the discharge capacity is recorded as SOC = (discharge capacity / standard capacity) * 100%. After discharge, three 0.2C charge and discharge cycles are performed again, and the last discharge capacity SOH = (discharge capacity / standard capacity) * 100% is recorded. The test results are shown in Table 2.

[0070] Table 2

[0071]

[0072] From the test results of Examples 1, 6 to 9 and Comparative Examples 1 and 2 in Table 2, it can be seen that although pure polyaniline coating the negative electrode active material improves the battery self-discharge performance, the discharge SOH decreases due to the poor conductivity of polyaniline in alkaline electrolyte. Similarly, the higher the proportion of polyethylene glycol in polyethylene glycol-polyaniline, the better the hydrophilic conductivity of the coating layer, and the smaller the impact of discharge SOH, but when the polyethylene glycol content is too high, the self-discharge performance decreases. From the test results of Examples 1 to 5, it can be seen that the thicker the coating layer, the smaller the dissolution and corrosion of the negative electrode active material, the higher the self-discharge SOC, and at the same time, the fewer zinc ions dissolved in the electrolyte and transferred to the positive electrode, the better the recovery SOH. However, when the thickness of the coating layer is too high, the self-discharge performance and discharge SOH are no longer well improved. From the test results of Example 1, Examples 12 to 15, Comparative Examples 1 and Comparative Examples 3, it can be seen that sodium phytate can effectively capture the zinc ions that are continuously dissolved and precipitated from the chelated negative electrode, preventing the zinc ions from being transmitted to the interlayer spacing of the positive electrode nickel hydroxide, causing irreversible decay of the positive electrode capacity. Therefore, the higher the proportion of sodium phytate in the electrolyte, the better the capacity recovery SOH after high-temperature storage.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode material for a nickel-zinc battery, characterized in that: The invention comprises zinc oxide and a coating layer coated on the surface of the zinc oxide, wherein the coating layer comprises a polyethylene glycol-polyaniline copolymer; and the thickness of the coating layer is 10-20 nm; The preparation of the polyethylene glycol-polyaniline copolymer comprises the following steps: Dispersing polyethylene glycol, aniline and dodecylbenzene sulfonic acid in water to obtain an emulsion; adding ammonium peroxodisulfate to the emulsion to react and obtain a polyethylene glycol-polyaniline copolymer; The molar ratio of the polyethylene glycol, aniline, dodecylbenzenesulfonic acid and ammonium peroxodisulfate is (0.5-2): (0.5-2): (2-5): (0.5-2); The molecular weight of the polyethylene glycol is 200-600 g / mol.

2. The negative electrode material for nickel-zinc batteries according to claim 1, characterized in that: The mass ratio of the zinc oxide to the polyethylene glycol-polyaniline copolymer is (8-15):

1.

3. The method for preparing a negative electrode material for a nickel-zinc battery according to claim 1 or 2, characterized in that: The following steps are involved: The polyethylene glycol-polyaniline copolymer and zinc oxide are dispersed in a solvent, filtered and dried to obtain zinc oxide coated with the polyethylene glycol-polyaniline copolymer.

4. A negative electrode sheet, characterized in that: It comprises a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises the negative electrode material for a nickel-zinc battery according to claim 1 or 2, or the negative electrode material for a nickel-zinc battery prepared by the method for preparing the negative electrode material for a nickel-zinc battery according to claim 3.

5. The negative electrode sheet according to claim 4, characterized in that: The active material layer includes 55% to 60% of zinc oxide coated with polyethylene glycol-polyaniline copolymer, 5% to 10% of zinc powder, 1% to 5% of calcium zincate, 0.5% to 2% of bismuth oxide, 0.05% to 0.1% of indium oxide, 0.01% to 0.5% of sodium dodecylbenzene sulfonate, 1% to 2% of chopped fibers and 25% to 30wt% of a binder.

6. A battery, characterized in that: The invention comprises a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet according to claim 4 or 5; the electrolyte comprises a hydroxide having a formula of M (OH), wherein M is selected from one or more of K, Na, Li, Al and Zn.

7. The battery according to claim 6, characterized in that The electrolyte also includes one or more of ZnO, a buffer, and sodium phytate.

8. The battery according to claim 7, characterized in that The buffer comprises phosphate; And / or, the molar concentration of ZnO in the electrolyte is 0.3M~1M; And / or, the molar concentration of sodium phytate in the electrolyte is 0.05M~0.3M.

9. The battery according to claim 7, characterized in that The injection amount of the electrolyte is 20% to 30% of the sum of the mass of the positive electrode sheet and the negative electrode sheet.

Citation Information

Patent Citations

  • Polypyrrole-clad nano spherical zinc oxide material and preparation method

    CN107275611A